PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 1 MATA PELAJARAN BAHASA INDONESIA DI SD NEGERI SAWAH BESAR 01 - Nita Khusnun Nandifa; Duwi Nuvitalia; Mira Azizah; Diah Saraswati (STKIP Subang, 2023)
SD Negeri Sawah Besar 01 in the subject of Indonesian Language Chapter 7 (I Want) whose results do not meet the minimum completeness criteria, learning is still conventional, does not apply innovative learning models, thus making students passive. Improving learning by applying the Problem Based Learning (PBL) learning model aims to improve student learning outcomes in the subject of Indonesian Language Chapter 7 (I Want). The research subjects were class I students of SD Negeri Sawah Besar 01 with a total of 29 students consisting of 15 boys and 14 girls. Classroom action research was carried out in two cycles, each cycle consisting of the stages of planning, implementing, observing, and reflection. Research techniques using observation techniques, evaluation test as well as documentation and descriptive research methods. The results of the study show that applying the Problem Based Learning (PBL) model can improve student learning outcomes in Indonesian Chapter 7 (I Want). The results of the pre-cycle evaluation test, which was originally a class average of 69, increased to 93 in cycle 1, and in cycle 2 to 99. With KKM 70 the average pre-cycle completeness was 66%, cycle 1 became 93%, and cycle 2 became 100%. From the results of the study it was concluded that the application of the Problem Based Learning (PBL) model could improve the learning outcomes of class 1 students at SD Negeri Sawah Besar 01 in the subject of Indonesian Language Chapter 7 (I Want).